Relationship of the level of self-esteem and injuries in young sambists - Shumova N.S. ,; Cuj Ciankun, (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assess the relationship between the level of self-esteem and other psychological factors with the severity and frequency of injuries among sambo wrestlers aged 18-25 years. Methods and structure of the study. To obtain empirical data, the following methods were used: Rosenberg self-esteem scale; emotional burnout questionnaire T.D. Radecke, and A.L. Smith (ABQ, 2001); Situational Motivation Scale (SIMS); self-assessment of an individuals readiness for a fight using 7 indicators; assessment of the effectiveness of athletes competitive activities (competition statistics); assessment of the frequency of injuries to athletes (statistics of injuries during the training, competitive process and in everyday life). The study was conducted at sports universities in Russia and China. Results and conclusions. Russian sambo wrestlers have a lower number of injuries, and performance and satisfaction with the result increases with: high, but differentiated self-esteem, including low self-esteem of readiness to use new, not fully mastered techniques and fight with an opponent who offers strong resistance, as well as one’s ability to accept time of a duel of deliberate decisions, autonomous identity (high identification regulation, low external regulation, high internal motivation for sports activities). The combination of high levels of identification and external regulation under more complex conditions (combination of educational and sports activities by Chinese sambo wrestlers training in Russia) leads to the suppression of fear of an opponent, victim behavior, and an increase in the number of severe injuries (spine). For Chinese sambo wrestlers training in China, the combination of youth, high levels of undifferentiated self-esteem, identification and external regulation with high training and competitive loads, a large number of prizes, increases the level of emotional burnout, and contributes to the rapid devaluation of achievements.